The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.14414/jebav.v17i1.265
|View full text |Cite
|
Sign up to set email alerts
|

Determinant factors of investors� behavior in investment decision in Indonesian capital markets

Abstract: This study examines the effect of financial information, macro environment, and subjective norms on investors behavior when making investment decisions in Indonesian capital market. It was conducted by a survey design and involved 190 individual investors in three big cities in Indonesia (Jakarta, Surabaya, and Bandung). By using Structural Equation Modeling with Warp-PLS 3.0, the results showed that macro factors had a significantly positive effect on the technical information, the financial information and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
4
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 6 publications
8
4
0
2
Order By: Relevance
“…The results of this research that contrasted with previous studies showed that coupons, tenors, and ease of buying retail bonds did not necessarily influence the intention of employees to invest. In Listyarti and Suryani (2014), the perceived behavioural control influenced the intention of selecting the stock, which was in line with this study. The use of funds derived from their funds also made for a consideration in investing.…”
Section: The Effect Of Product Involvement On the Intention Of Employees To Invest In Retail Bond Productssupporting
confidence: 88%
“…The results of this research that contrasted with previous studies showed that coupons, tenors, and ease of buying retail bonds did not necessarily influence the intention of employees to invest. In Listyarti and Suryani (2014), the perceived behavioural control influenced the intention of selecting the stock, which was in line with this study. The use of funds derived from their funds also made for a consideration in investing.…”
Section: The Effect Of Product Involvement On the Intention Of Employees To Invest In Retail Bond Productssupporting
confidence: 88%
“…Prior to the Covid-19 pandemic, subjective norm had no effect on investing intention of investors. This is in line with the results of the research by Listyarti & Suryani (2014) which concluded that subjective norms have no effect on investment intentions in the Indonesian capital market. Ejigu & Filatie (2020) from the results of their research also conclude the same thing, namely subjective norms was not statistically significant in affecting intention though it has a negative relationship with the intention to invest.…”
Section: Discussionsupporting
confidence: 91%
“…The results of research by Rahadjeng& Fiandari (2020) show that attitude, subjective norms and behavioral control have an influence on the intention to invest in share investment. This is in line with the research results of Pahlevi & Oktaviani (2018), Listyarti & Suryani (2014) and Seni & Ratnadi (2017) which concluded that the attitude, subjective norm, perception of behavior control, have positive effect on investors' intention in investing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of these phenomena in the financial market is the probable reason why the failure of risk management system is based on the neoclassical assumptions of normal distributions (Chittedi, 2014). Within the literature, researches in the financial market are moving towards the behavioural aspects of investment rather than adhering to the fundamental or traditional approaches (Listyarti & Suryani, 2014;Olokoyo, Oyewo, & Babajide, 2014;Sandberg, Hutter, Richetin, & Conner, 2016). With an alternative perspective looking at human behaviour, the paradigm of behavioural finance can thus shift to looking at other theories that are open to the multidisciplinary understanding of human behaviour (Tuyon & Ahmad, 2016).…”
Section: Introductionmentioning
confidence: 99%